A development framework for the consultant radiographer in oncology: the Leeds experience. Issue 2 (4th March 2016) - Roberts, Neill
Abstract: The role of the consultant radiographer in radiotherapy is a relatively new concept and to date the number of post holders in these roles remains low. Despite challenges to role creation for the non-medical consultant, the benefits of role development and skill mix within the national health service are evident. Among these challenges is the need to ensure appropriate and credible training of the consultant radiographer. This case study focusses on the local experience of developing a suitable competency framework for the first Consultant Radiographer at the Leeds Cancer Centre. It highlights elements of the framework that equip the post holder to carry out the role and how the governance underpinning such a framework could be used by other radiotherapy centres across the United Kingdom.